PENANGANAN ANAK ADHD (Attention Deficit Hiperactivity Disorder) STUDI KASUS PAUD IT MUTIARA CENDEKIA KOTA LUBUKLINGGAU - Umar Diharja; Rini Sugiarti, Erwin Erlangga (CV. Adiba Aisha Amira, 2025)
This research seeks to examine the implementation of inclusive education principles in Early Childhood Education institutions concerning children with ADHD (Attention Deficit Hyperactivity Disorder) and the impact of these approaches on the child's overall development. Hyperactive conduct renders youngsters incapable of remaining seated, executing tasks autonomously, and adhering to instructions from the teacher. Children with ADHD struggle to concentrate on their studies due to an inability to focus, a lack of attentiveness to instructor directions, and difficulties remaining still. A case study at PAUD IT Mutiara Scholar Lubuk Linggau examined the management of children with ADHD within the implemented learning process. This research employs a descriptive qualitative method utilizing a case study approach to furnish a comprehensive grasp of the occurrences encountered by the subjects of the study. The research findings elucidate the correlation between the management of children with ADHD in educational settings and the strategies that promote their developmental growth in alignment with their chronological age. The function of institutions in managing children during teaching and learning activities in schools is anticipated to impact children's behaviors and attitudes. The teacher's responsibility for students with ADHD encompasses educating, instructing, guiding, directing, training, and assessing. Third, the involvement of parents in the education of children with ADHD, fostering social and emotional bonds, is crucial for addressing the child's deficiencies.